Jejak Pragmatisme dalam Politik di Indonesia (Era 2009 – 2017) - Miftah Faried Hadinatha (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
This paper will analyze pragmatism in the political world in Indonesia. Pragmatism is a modern philosophical movement, it was initiated in United States, by C.S. Pierce who was inspired by Immanuel Kant. Pragmatism developed through the thoughts of some figures such as John Locke, Gorge Berkley, David Hume, William James and John Dewey. Pragmatism assumes that truth, meaning and the value of an idea must be based on practical aspects. Based on this assumption, the author has a hypothesis that what happens in the political world in Indonesia is full of pragmatism. At least this condition can be found in several important aspects such as; the attitude of those politicians that looks massively toward the elections, the party coalitions, while serving in government and the culture of political dynasties. This phenomenon describe that politics in Indonesia is in degradation of ethical values, even from the state of  ideology (Pancasila), norms of life and especially from the religious side. This pragmatic attitude is allegedly close to hedonism. The paper was completed with a literature review, by referring to the news about politics in Indonesia since 2009 until 2017. After reviewing an authoritative reference, the authors conclud that pragmatism was ingrained in the practice of political life in Indonesia. Indeed the practice of pragmatic politics is not hesitant to do by who has an interest in politics. Surely this will damage the order of life, and certainly also in the contrary to the values of religiosity, especially Islam as the teachings adopted by the majority of pragmatic political actors.